Estimativa da erosão hídrica nas bacias hidrográficas dos rios Lontra e Manuel Alves Pequeno, TO - Barros, Enicléia Nunes de Sousa (Universidade Federal do Tocantins, 2017)
The hydraulic erosion is one of the main processes of soil degradation. It brings about impacts which range from productivity reduction to existing natural resources decrease. This way, the present work had the objective to evaluate the effects of the alternations in soil use from 1990 to 2007, applying RUSLE model to estimate the soil erosion behavior in space to the hydrographic basins of the Lontra River and Manuel Alves Pequeno River – TO. The hydraulic erosion of the Lontra River basin in 2007 ranged from “light” (51,3%), in the basin central region, where the land is flat and the predominant soil is native wood, to “extremely high” (24,6%) from north to west with land use predominantly by livestock and bending soil surface. In the Manuel Alves Pequeno River basin, in the same period, the erosion classified as “light” (52%) is distributed along the basin, due to most of the soil presents low erosion properties and most of the land is covered by cerrado. As for the “extremely high” (6,7%) in the north and west, it occurred due to the land being used by livestock and in the east, due to being more bending. The seasonal evaluation of the soil loss evidenced that there were no significant variations while carrying out these studies. However, in the Lontra River basin, from 2000 to 2007, there was a reduction of 0,3% in the “extremely high” class due to the advance of the cerrado over the cattle ranch, while in the Manuel Alves Pequeno River basin, from 1990 to 2007, there was a gradual increase on the erosion level, with the addition of the “high”, “very high” and “extremely high” classes, ranging from 25% to 26,4%, explained by the growth of pastoral activities in this basin. The critical points with higher soil susceptibility to erosion, found in this work, become fundamental tools to make decisions associated to the management preservation and planning the soil use.